Synergistic effect of SBS copolymers and aromatic oil on the characteristics of asphalt binders and mixtures containing reclaimed asphalt pavement - Eltwati, Ahmed Salama; Al-Saffar, Zaid Hazim; Azman, Mohamed; Mohd Rosli, Hainin; Elnihum, Ahmed; Enieb, Mahmoud (Elsevier Ltd, 2022)
Rejuvenators have been utilized to restore the physical and rheological properties of aged asphalt binders found in the reclaimed asphalt pavement (RAP). Also, the rejuvenators are utilized to enhance the cracking resistance of asphalt containing RAP. In addition, polymers have been efficiently applied to enhance the rutting performance of rejuvenated mixtures. The purpose of this study was to assess the influence of combining SBS copolymers and aromatic oil (AO) at the same time as a hybrid rejuvenator (HR) on the performance of high RAP asphalt binders and mixtures. HR is a mixture of 25% SBS and 75% AO. The properties of the rejuvenated binders were assessed by SARA (Saturates, Asphaltene, Resin, and Aromatics) fractions analysis, Fourier Transform Infrared Spectrum (FTIR), physical tests, high-temperature storage stability test, Dynamic Shear Rheometer (DSR) test, and Bending Beam Rheological (BBR) test. In addition, the mechanical behaviour of the rejuvenated mixtures was assessed using the Indirect Tensile Strength (ITS) test, moisture susceptibility test, resilient modulus test, and wheel tracking rutting test. The results showed that appropriate adjustment of the SARA fractions and SBS copolymer could improve the overall performance of mixtures and binders with high RAP content. However, it is asserted that a field investigation of this compound rejuvenator should be done to further analyze its influence on the long-term field behavior of high RAP mixtures.